Cervical melioidosis: an infrequent cause of neck abscess - Binti Azwan, Nurul Alya; Shanmugam, Ram Kumar Sharma; Teng, Kong Yin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Melioidosis remains as one of the rare infectious disease with high mortality and morbidity rate. It is caused by the gram-negative bacilli Burkholderia pseudomallei found in soil and water. We would like to share our experience of four case series that had been collected in Bintulu Hospital, Sarawak over a period of eight months starting from June 2018- January 2019. A total of four patients presented with neck abscess where the pus culture and sensitivity show B. pseudomallei but the blood culture and sensitivity show no culture or growth.